STAT3 signalling pathway is implicated in keloid pathogenesis by preliminary transcriptome and open chromatin analyses. Issue 4 (29th April 2019) - Lee, Yun‐Shain; Liang, Ya‐Chen; Wu, Ping; Kulber, David A.; Tanabe, Kylie; Chuong, Cheng‐Ming; Widelitz, Randall; Tuan, Tai‐Lan
Abstract: Keloids are wounding‐induced fibroproliferative human tumor‐like skin scars of complex genetic makeup and poorly defined pathogenesis. To reveal dynamic epigenetic and transcriptome changes of keloid fibroblasts, we performed RNA‐seq and ATAC‐seq analysis on an early passage keloid fibroblast cell strain and its paired normal control fibroblasts. This keloid strain produced keloid‐like scars in a plasma clot‐based skin equivalent humanized keloid animal model. RNA‐seq analysis reveals gene ontology terms including hepatic fibrosis, Wnt‐β‐catenin, TGF‐β, regulation of epithelial‐mesenchymal transition (EMT), STAT3 and adherens junction. ATAC‐seq analysis suggests STAT3 signalling is the most significantly enriched gene ontology term in keloid fibroblasts, followed by Wnt signalling (Wnt5) and regulation of the EMT pathway. Immunohistochemistry confirms that STAT3 (Tyr705 phospho‐STAT3) is activated and β‐ catenin is up‐regulated in the dermis of keloid clinical specimens and keloid skin equivalent implants from the humanized mouse model. A non‐linear dose‐response of cucurbitacin I, a selective JAK2/STAT3 inhibitor, in collagen type I expression of keloid‐derived plasma clot‐based skin equivalents implicates a likely role of STAT3 signalling in keloid pathogenesis. This work also demonstrates the utility of the recently established humanized keloid mouse model in exploring the mechanism of keloid formation.